Evaluation of Phenol Transport Using Polymer Inclusion Membrane (PIM) with Polyeugenol as a Carrier - Arifina Febriasari; Dwi Siswanta; Agung Abadi Kiswandono; Nurul Hidayat Aprilita (Jurnal Rekayasa Kimia & Lingkungan, 2016)
A recovery study of phenol with Polymer Inclusion Membranes (PIMs) needs to be evaluated to determine values of transport kinetic parameter, level of stability, and selectivity of the membrane. This paper describes results of the evaluation of phenol transport using PIMs with polyeugenol as a carrier. PIMs were made by mixing polyeugenol, dibenzylether, and polyvinylchloride in a solvent (tetrahydrofuran) then printed in a container with diameter 4.5 cm and allowed to vaporize for 72 hours. Further evaluation studies are conducted at pH 4.5 with various parameters, among of them are various times that were taken to identify parameters of the transport kinetics of phenol, membrane stability, characterization, and testing of membrane selectivity by comparing transport of phenol with another compound, in this study chromium is used. This study results in calculation of values of transport kinetics of membrane permeability obtained at 8.8 x 10-5 m/s, flux value of 9.512 x 10-4 g/m2s, and diffusion coefficient of 3.826 x 10-11 m2/s. Repeating use over three times, 48 hours, indicates reduction in power of phenol transport by 70.81%. While selectivity test indicates that membrane is used more selectively against phenol than chromium metal. Based on study results, phenol transport effectiveness using PIM with polyeugenol as carrier is 91.4% in optimum condition.